Operation results of a 100 kW class reformer for molten carbonate fuel cell - Seo, Hai-Kyung; Eom, Young-Chang; Kim, Young-Chun; Lee, Sang-Deuk; Gu, Jae-Hoi (ELSEVIER SCIENCE BV, 2007)
The performance and operation results of the reformer that supplies synthesis gases to a 100 kW class molten carbonate fuel cell are reported. A CH4 conversion ratio of 95.6%, a CO conversion ratio of 31.2%, a reforming reaction temperature of 745 degrees C and a produced hydrogen rate of 70.7 Nm(3) h(-1) are obtained from a comparison of post gas analysis and theoretical estimation of thermodynamics at 87.6 h. To calculate the efficiency, the Cycle-Tempo 5.0 program is used. The thermal efficiency of the designed system is 61.1% and the real thermal efficiency of the system is 44.5% at 108 h. The low thermal efficiency is mainly attributed to supplying excess fuel to meet the outlet temperature of the reforming reactors. In the present system, the outlet temperature of the reforming reactors appears to be below the temperature required at the stack of molten carbonate fuel cell (MCFC), that is, over 580 degrees C. In order to maintain the outlet temperature of the reforming reactor over 580 degrees C, it is necessary to heat the reformed gases at the convection zone of combustion gases. For higher thermal efficiency, the combustion space and the excess fuel should be reduced until reaching minimum temperature of the surface of reforming tube, at which point has no influence on the CH4 conversion ratio. (c) 2007 Published by Elsevier B.V.
Keywords: HYDROGEN; GAS